IMPLEMENTASI METODE DESIGN THINGKING DALAM PERANCANGAN UI/UX PADA WEBSITE SIKATAMA UNIVERSITAS ISLAM NEGERI (UIN) RADEN FATAH PALEMBANG - Fenny Purwani; M. Ridho Karunia; Ramdan Eka Saputra; M. Abdus Salam (Jurnal Riset Teknik Komputer, 2024)
This study discusses the implementation of the Design Thinking method in the UI/UX design of the SIKATAMA (Student ID Information System) website at UIN Raden Fatah Palembang, aimed at addressing issues such as the difficulty in accessing physical Student ID Cards (KTM), concerns about personal data security, and the non-intuitive interfaces of other campus systems. SIKATAMA is a platform that facilitates the creation and management of digital KTM, serving as the official identity for students within the campus environment. The Design Thinking method was chosen for its user-centered approach, with the goal of improving the user experience and ease of website use, allowing students to access KTM-related information more conveniently. This study follows the five stages of Design Thinking: empathize, define, ideate, prototype, and test. The results of this research are expected to deliver a more intuitive interface and enhance student interaction and ease of use in managing KTM services digitally through the SIKATAMA website.